P190 Implementation of IBD symptom diary – Case Finnish IBD register. (21st January 2022) - Mustonen Real World Data Manager, A; Asikainen, S; Toivonen, T; Jussila, A T
Abstract: Background: BCB MyHealth application is a digital monitoring system of patient reported outcomes (PROMs) fully integrated and synchronized with the Finnish IBD Register, which delivers information about the patients' disease and state of health. Our system monitors patients' symptoms and well-being only at one point. There is a need to monitor patients' symptoms and well-being more closely between follow-up visits. Therefore, we developed a digital daily self-monitoring symptom diary service, Feeling application, which is suitable for all patients with IBD in everyday practice. In addition, our goal was to create a system that allows IBD-patients to view their own parameters used to monitor treatment. Methods: As a part of MyHealth, we developed the Feeling app (Figure 1) with Tampere University Hospital. Project group included gastroenterologists, IBD-nurses, and the hospitals' senior medical advisor of health technology assessment. The Feeling app is a digital daily self-monitoring symptom diary service intended for IBD-patients. The system supports biometric authentication (Figure 2) and saves responses to IBD Register database. Figure 1. IBD Symptom Diary Figure 2. Biometric authentication Results: Feeling app enables continuous home-monitoring of patients with IBD. This symptom diary allows patients to monitor their symptoms and well-being daily. They can see their own answers and how their symptoms and well-being have developed weekly, monthly, or annually. During treatment follow-up, the Feeling app also visualizes lab parameters used to monitor treatment, such as CRP, calprotectin and hemoglobin values, which are derived from the IBD register (Figure 3). In addition, certain endoscopy related parameters, such as SES-CD and Mayo Score are visualized for the patient. Health care professionals (HCPs) can see summary view all the data that the patient has inserted in the Feeling app in IBD register and the data is visualized in real time. Tampere University Hospital started to use the Feeling app in 2021. Figure 3. Summary view Conclusion: The Feeling app provides new ways to support patient care and is an efficient tool for long-term data collection. The opportunity of patients to monitor the development of their symptoms and well-being, and to see the lab parameters used to monitor treatment may improve adherence to treatment. With efficient data collection we have increased opportunity to utilize the data for AI activities such as synthetic data and outcomes prediction.